PERSAMAAN STATUS LAKI-LAKI DAN PEREMPUAN DALAM PANDANGAN ALLAH MENURUT 1 KORINTUS 11:7-11: Indonesia - Hasahatan Hutahaean; Yusuf L. M.; Arung P Marumbona; Nurliani Siregar (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
In ancient near eastern times, the phenomenon of status differences or degrees between men and women was considered normal. Even at the time of Jesus, this phenomenon was still powerful. In the religious community, this difference can still be seen by referring to one of the texts of 1 Corinthians 11:7-12. In the text, it can be seen that there is an emphasis on the different positions of men and women who are considered wildly different when they enter into a fellowship. However, theologically all humans are equal before God. Can it be said that it is just and right if this phenomenon continues to be maintained without a more robust and biblical reason? For a reason, analysis verses 7-12, the meaning of the text and context does not emphasize the differences in the degrees of men and women. Instead, it emphasizes the equality of status in the sight of God. Even if women had to cover their heads when entering the worship room at the time, that only referred to the customs or culture of that era which emphasized the element of politeness in the community so that women would not become a stumbling block in the fellowship.